Le droit des coopératives en Afrique Réflexions sur l'Acte uniforme de l'OHADA - Tadjudje, Willy (RESSOR, 2021)
"The aim of this book is to analyse the level of implementation of the Uniform act on cooperatives (Acte uniforme relatif au droit des sociétés coopératives, AUSCOOP) ten years after its enactment. The authors' analysis, conclusions and recommendations lead to two main ideas: on the one hand, the need to correct the weaknesses and inconsistencies of the Act, and on the other hand, the lack of coherence of the Act with the area's legal environment.